Bridging cognitive skills and environmental awareness: critical and creative thinking as predictors of digital ecoliteracy - Hasibuan, Saberina; Yustina, Yustina; Wahyuni, Resma (Frontiers in Education, 2025)
Digital ecoliteracy, the ability to access, critically evaluate, and apply environmental information through digital platforms, is increasingly recognized as a critical competency for addressing twenty first-century sustainability challenges. This study aims to explore how critical and creative thinking predict digital ecoliteracy among Indonesian university students. Two independent samples of university students (Sample 1: N = 45; Sample 2: N = 60) participated in the study. The relationship between critical thinking, creative thinking, and digital ecoliteracy was examined using Pearson and Spearman correlations. Multiple regression analyses were conducted to assess the predictive power of these cognitive skills on digital ecoliteracy. The analysis revealed that critical thinking had strong positive correlations with digital ecoliteracy (r = 0.717–0.755, p < 0.01), while creative thinking showed moderate to strong correlations (r = 0.233–0.709, p < 0.05–0.01). Multiple regression analysis confirmed that both cognitive skills significantly predicted digital ecoliteracy, jointly explaining 72–75% of the variance (Sample 1: R2 = 0.721, β = 0.689 for critical, β = 0.394 for creative; Sample 2: R2 = 0.750, β = 0.457 for critical, β = 0.592 for creative; p < 0.001). The results indicate that fostering higher-order cognitive skills such as critical and creative thinking is a robust pathway for enhancing sustainability-oriented digital competencies. These findings align with UNESCO's Education for Sustainable Development and the OECD's Learning Framework 2030, emphasizing the pivotal role of educators in facilitating digital ecological engagement. The study also highlights the need for mixed-methods research to explore the causal mechanisms underlying these relationships and addresses the limitations of a quantitative-only approach.